2019
DOI: 10.2169/internalmedicine.2997-19
|View full text |Cite
|
Sign up to set email alerts
|

Renin-angiotensin System Blockade Therapy for Early Renal Involvement in MYH9-related Disease with an E1841K Mutation

Abstract: MYH9-related disease is a rare genetic disorder characterized by macrothrombocytopenia, with frequent proteinuric nephropathy, hearing loss, and cataract. Although proteinuric nephropathy usually progresses to renal failure, there is no established treatment for the nephropathy. We herein describe the case of a 19-year-old man carrying an E1841K MYH9 mutation, who developed persistent proteinuria. The patient was diagnosed with early-stage MYH9-related nephropathy based on the histological examination of a kid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The comparison between the two NMMHC‐IIA domains (head and coil/tail) confirmed that head variants are associated with a higher occurrence of nephropathy and sensorineural deafness than coil/tail variants, but no significant difference was found for cataracts 14 . Depending on the site of the MYH9 variants, it has been suggested that the initiation of renin–angiotensin system inhibitors may decrease proteinuria and delay the progression of renal damage 15–18 . This information suggests that early and correct diagnosis of MYH9 ‐RD is essential.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The comparison between the two NMMHC‐IIA domains (head and coil/tail) confirmed that head variants are associated with a higher occurrence of nephropathy and sensorineural deafness than coil/tail variants, but no significant difference was found for cataracts 14 . Depending on the site of the MYH9 variants, it has been suggested that the initiation of renin–angiotensin system inhibitors may decrease proteinuria and delay the progression of renal damage 15–18 . This information suggests that early and correct diagnosis of MYH9 ‐RD is essential.…”
Section: Discussionmentioning
confidence: 91%
“…14 Depending on the site of the MYH9 variants, it has been suggested that the initiation of renin-angiotensin system inhibitors may decrease proteinuria and delay the progression of renal damage. [15][16][17][18] This information suggests that early and correct diagnosis of MYH9-RD is essential.…”
Section: Discussionmentioning
confidence: 99%
“…Should signs of initial kidney damage appear, patients have to receive angiotensin converting enzyme inhibitors and/or angiotensin receptor blockers, because these drugs have been reported to have a beneficial effect. 86 , 87 …”
Section: Management Of the Manifestations That Add To Thrombocytopeniamentioning
confidence: 99%
“…53 In these cases, the early administration of angiotensin II receptor type 1 (AT1) antagonists may have beneficial effects. 54…”
Section: Diagnostic Approachesmentioning
confidence: 99%